Airborne HSRL-2 measurements of elevated aerosol depolarization associated with non-spherical sea salt - Ferrare, Richard; Hair, Johnathan; Hostetler, Chris; Shingler, Taylor; Burton, Sharon P.; Fenn, Marta; Clayton, Marian; Scarino, Amy Jo; Harper, David; Seaman, Shane; Cook, Anthony; Crosbie, Ewan; et al. (Frontiers in Remote Sensing, 2023)
Airborne NASA Langley Research Center (LaRC) High Spectral Resolution Lidar-2 (HSRL-2) measurements acquired during the recent NASA Earth Venture Suborbital-3 (EVS-3) Aerosol Cloud Meteorology Interactions over the Western Atlantic Experiment (ACTIVATE) revealed elevated particulate linear depolarization associated with aerosols within the marine boundary layer. These observations were acquired off the east coast of the United States during both winter and summer 2020 and 2021 when the HSRL 2 was deployed on the NASA LaRC King Air aircraft. During 20 of 63 total flight days, particularly on days with cold air outbreaks, linear particulate depolarization at 532 nm exceeded 0.15-0.20 within the lowest several hundred meters of the atmosphere, indicating that these particles were nonspherical. Higher values of linear depolarization typically were measured at 355 nm and lower values were measured at 1064 nm. Several lines of evidence suggest that these nonspherical particles were sea salt including aerosol extinction/backscatter ratio (“lidar ratio”) values of 20-25 sr measured at both 355 and 532 nm by the HSRL-2, higher values of particulate depolarization measured at low (<60%) relative humidity, coincident airborne in situ size and composition measurements, and aerosol transport simulations. The elevated aerosol depolarization values were not correlated with wind speed but were correlated with salt mass fraction and effective radius of the aerosol when the relative humidity was below 60%. HSRL 2 measured median particulate extinction values of about 20 Mm-1 at 532 nm associated with these nonspherical sea salt particles and found that the aerosol optical depth (AOD) contributed by these particles remained small (0.03-0.04) but represented on average about 30-40% of the total column AOD. Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) spaceborne lidar aerosol measurements during several cold air outbreaks and CALIOP retrievals of column aerosol lidar ratio using column AOD constraints suggest that CALIOP operational aerosol algorithms can misclassify these aerosols as dusty marine rather than marine aerosols. Such misclassification leads to ~40-50% overestimates in the assumed lidar ratio and in subsequent retrievals of aerosol optical depth and aerosol extinction.